PSYCHOLOGICAL INTERVENTION IN INTERNAL AUDITS: ANALYSING STAKEHOLDER BEHAVIOUR AND ITS IMPACT ON INTERNAL AUDITOR INDEPENDENCE IN PUBLIC FINANCIAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FROM 2022-2024 WITHIN THE BEHAVIOURAL ACCOUNTI - Dhani Wirianto (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study investigates how psychological interventions by stakeholders can influence the independence of internal auditors in the financial sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2022-2024, and explores the moderating role of whistleblowing protection in this context. The main focus of this research is to analyse the mechanisms of psychological intervention and its impact on auditor independence, as well as to test whether whistleblowing protection effectively mitigates the negative effects caused by such interventions. Using a quantitative approach, the study adopts a causal-comparative survey design and involves 150 internal auditors selected through stratified random sampling from financial sector companies listed on the IDX. Data were collected using a Likert scale questionnaire, which was then analysed through multiple linear regression and Structural Equation Modelling (SEM) to examine the relationships between the studied variables. The results indicate that psychological interventions negatively affect auditor independence, while whistleblowing protection plays a significant moderating role in reducing the impact of these interventions. This study contributes theoretically by enriching the literature on the psychological influence in auditing practices and auditor independence, and offers practical recommendations for whistleblowing protection policies that can strengthen auditor independence in the financial sector. The findings also provide additional insights into how effective internal policies can help mitigate the pressures auditors face while performing their duties with high objectivity